Turbulence around patriotism: philosophical perspective - Maria Małgorzata Boużyk (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The aim of the article is to determine the place of patriotism among other universal values and a philosophical reflection on its current formula. The analysis is based on the classical philosophy of Aristotle, Thomas Aquinas, J. Maritain, E. Gilson, J. Woroniecki, J. M. I. Bocheński, M. A. Krąpiec and John Paul II. The article consists of two parts. Part 1 poses several questions concerning patriotism in the light of ongoing cultural transformations. Part 2 deals with patriotism as a virtue according to classical ethics to propose answers to these questions.